2019
DOI: 10.1083/jcb.201712120
|View full text |Cite
|
Sign up to set email alerts
|

The AAA+ ATPase/ubiquitin ligase mysterin stabilizes cytoplasmic lipid droplets

Abstract: Mysterin, also known as RNF213, is an intracellular protein that forms large toroidal oligomers. Mysterin was originally identified in genetic studies of moyamoya disease (MMD), a rare cerebrovascular disorder of unknown etiology. While mysterin is known to exert ubiquitin ligase and putative mechanical ATPase activities with a RING finger domain and two adjacent AAA+ modules, its biological role is poorly understood. Here, we report that mysterin is targeted to lipid droplets (LDs), ubiquitous organelles spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 26 publications
4
97
0
Order By: Relevance
“…Previous studies showed that RNF213 oligomerizes via its ATPase domain (Morito et al, 2014) and has ubiquitin ligase activity (Banh et al, 2016;Kobayashi et al, 2015). ATPase activity also has been implicated in recruitment to, and stabilization of, lipid droplets (Sugihara et al, 2019). However, the type of UB linkages added by RNF213, the cooperating E2(s), and the role(s) of the AAA-ATPase and E3 domains in MMD pathogenesis have remained unknown or controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that RNF213 oligomerizes via its ATPase domain (Morito et al, 2014) and has ubiquitin ligase activity (Banh et al, 2016;Kobayashi et al, 2015). ATPase activity also has been implicated in recruitment to, and stabilization of, lipid droplets (Sugihara et al, 2019). However, the type of UB linkages added by RNF213, the cooperating E2(s), and the role(s) of the AAA-ATPase and E3 domains in MMD pathogenesis have remained unknown or controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of larger panels of RNF213 alleles will be required to solidify these findings. A recent study suggested that RNF213 localizes to and stabilizes lipid droplets (Sugihara et al, 2019). Furthermore, RNF213 also stabilizes the droplets by removing ATGL (a lipase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, mysterin/RNF213 is a AAA ATPase with a ubiquitin ligase domain, which is implicated in signaling pathways involved in vascular development that supports cancer growth and metastasis (106,107). Interestingly, mysterin is also involved in the stabilization of lipid droplets, which are regulated by SEPT9 in cells that are infected by the hepatitis C virus (108,109).…”
Section: Functional Clustering Of the Sept9 Proteome Points To Isoformentioning
confidence: 99%
“…Furthermore, how cells sense lipid peroxidation and mount an orchestrated multi-organelle response to maintain lipid homeostasis remains poorly understood, but is likely critical to our understanding of many diseases. Indeed, new work continues to reveal disease-related proteins like Rab18, Snx14, and Mysterin that play unexpected but important roles in lipid metabolism and LD crosstalk with other organelles (13–15), but how these proteins work together to connect LDs with other cellular compartments requires further study.…”
mentioning
confidence: 99%